Childhood Vaccination Practices and Reflections on Medicolegal Evaluation - Nicel Yıldız Silahlı; Hızır Aslıyüksek; Kağan Gürpınar; Tülin Tiraje Celkan (Çocuk Dergisi)
Objective: Despite the known positive effects of vaccines on public health, claims about vaccines and vaccination processes continues to be a medicolegal problem. This study aims to evaluate the characteristics of childhood vaccination practices and reflections on medicolegal evaluation. Material and Method: This retrospective descriptive study evaluated the reports of the 7th Specialization Board of the Council of Forensic Medicine which were prepared between 2018-2021 after the approval of Scientific Research Committee of The Council of Forensic Medicine Scientific Research Commission. The data about claims related to vaccination were assessed. Numerical data were expressed as the median and interquartile range (IQR) for continuous variables and counts and proportions for descriptive variables. Results: The female/male ratio of the cases was found to be 7/6. The diagnoses which were claimed to have developed after vaccination in the cases were: cerebral palsy, Diabetes Mellitus, Subacute Sclerosing Panencephalitis (SSPE), local wound, transverse myelitis, brachial neuritis, abscess and osteomyelitis, seizure and blindness. Diphtheria, acellular pertussis, Tetanus, Inactive Polio, Hemophilus influenza Type B and Hepatitis B, Measles, BCG (Bacillus Calmette-Guerin), vaccinations were blamed. In the evaluation of the committee, “local wound, transverse myelitis and brachial neuritis” were defined as complications that may develop as a result of vaccination despite all due care and attention. In two cases, lack of care in the practices of health personnel was identified. Malpractice was not detected in other cases. Discussion/Conclusion: Healthcare professionals should have sufficient scientific knowledge about vaccinations to explain the adverse effects to parents.